Water temperature monitoring by using fiber bragg grating sensor - Nur Ainaa Adhreena, Muhamad Shukri; Mohd Hafizi, Zohari; Epin, Vorathin (2022)
Fiber Bragg grating (FBG) sensors have been widely utilized as a sensor for measuring strain, temperature, and vibration measurements. In this study, an optical FBG sensor system was developed to monitor the temperature fluctuation in water. The sensor was delicately packaged in order to eliminate the influence of strain acting on the sensor. The sensor had been submerged in iced water and the temperature was constantly increased by using an electric immersion heater. The experimental data were obtained to determine the temperature sensitivity of the FBG sensor. It is found that the relationship between the changes in temperature and changes in Bragg wavelength is virtually higher in linearity with R2= 0.9997 and has superior sensitivity which is 10.1 pm/°C. This finding proves that the FBG sensor could be a good candidate for temperature sensing devices.